How to reduce financial costs using renewable energies in developing countries - Rezaei, Gholamreza; Esmaeilvalizadeh; Kashani, Nader (The journal of contemporary issues in business and government, 2021)
A unique position is given to developing countries in achieving the socio-economic and environmental benefits of renewable resources as a means of adapting to energy demand in a sustainable way. Implementation of sustainable activities in developing countries have proven to be challenging, at least as much as in developed countries.The difficulty of attracting adequate and cost-effective investment is considered as one of the major barriers to implement renewable energy technologies in developing countries.This study examines the impact of investment costs on the prospects for renewable energy generation in developing countries. The present study presents a comprehensive analysis of developing countries, six renewable energy technologies and three fossil fuel-based power generationtechnologies. Accordingto the results, there are significant cost changes and a range under which renewables are deprived by current financial activities.The energy-economic model is used to illustrate how reducing financial costs improves the implementation of renewableresources. Also, according to the results of this study, climate policies reduce financial costs for renewable resources, which is an effective way to reduce greenhouse gas emissions.This study introduces new perspectives by using different scenarios to develop energy investment in developing countries and presents several conclusions for renewable energy policy makers and related projects developers and provides solutions for energy analysis and investment modeling.